The influence of the group investigation model assisted by media puzzles on students' understanding of science concepts - Agustin Khoirun Nisa; Sekar Dwi Ardianti; Nur Fajrie (Jurnal Pijar Mipa, 2023)
This research is based on students' misconceptions about science subjects, especially animal life cycle materials. This study aimed to find significant differences after applying the puzzle media-assisted group investigation model to students' understanding of science concepts. This research is a quantitative research experiment with a group pretest-posttest design. The sample used was grade V students of SDN 2 Wonosemi, consisting of 12 students. The sampling technique used is random sampling. The data collection method used is the test method. The instruments used are pretest and posttest questions of multiple choice understanding of student concepts consisting of 20 questions. The normality test is an initial test that shows normally distributed data. This study used an average difference test with a statistical test, namely the Paired Sample T-test. The t-test results showed that the average pretest score was 59.17 while the average posttest score was 82.92 with Sig. (2-tailed) = 0.00 < 0.05. According to the criteria used in the Paired Sample T-Test, Ha is accepted, and H0 is rejected. So, a significant difference exists between pretest and posttest scores using a group investigation model assisted by puzzle media on students' understanding of science concepts. Applying the group investigation model assisted by puzzle media affects the understanding of students' science concepts.